The Development of Moderate Class More Knowledge Activities of Lao Yao Wittayakarn School under the Secondary Education Service Area Office 26 - Rakpakdee, Duennapa; Promta, U-rasa; Pollharn, Chumnian (Journal for Developing the Social and Community, 2020)
The purposes of this research were to 1.) study the current situation and approach to develop Moderate Class More Knowledge activities of Lao Yao Wittayakarn School and 2.) to develop Moderate Class More Knowledge activities of Lao Yao Wittayakarn School. The research procedures were divided into two phrases. The first stage was to study the present situation and approach of development Moderate Class More Knowledge activities. The samples included 1 administrator, 1 supervisor, and 25 teachers. The statistics used for data analysis were mean, and standard deviation. The second stage was the studying of the development of Moderate Class More Knowledge activities. The target group was 18 Mattayomsuksa 3 students from Lao Yao Wittayakarn School. Action research was used to analyze the content for better evaluation. The results found that: 1. The Moderate Class More Knowledge activities of Lao Yoa Wittayakarn School in overall was high level by raking the from maximum to minimum average following 1) Hand Skill 2) Heart development activities 3) Health development activities and 4) Head development activities respectively. 2. The approaches for the development of Moderate Class More Knowledge activities were concluded as follow 1) the learners should practice with the authentic materials 2) the activities should be designed to support the learners’ desirable characteristic and self-esteem 3) the learners should be encouraged to take care of their health and practice in the real situations and 4) the activities should be more academic and the learners were able to present their feeling, understanding and idea. 3. The result of the development of Moderate Class More Knowledge activities of Lao Yoa Wittayakarn School was found in the researcher’s lesson plans in high level. On the other hand, the result of the studying the learners’ satisfying toward the Moderate Class More Knowledge activities was in the highest level.